Effect of Experiential Communication Skills Education on Graduate Medical Education Trainees' Communication Behaviors: A Systematic Review. (23rd November 2022) - Bylund, Carma L.; Vasquez, Taylor S.; Peterson, Emily B.; Ansell, Margaret; Bylund, Kevin C.; Ditton-Phare, Philippa; Hines, April; Manna, Ruth; Singh Ospina, Naykky; Wells, Robert; Rosenbaum, Marcy E.
Abstract : Purpose: A better understanding of how communication skills education impacts trainees' communication skills is important for continual improvement in graduate medical education (GME). Guided by the Kirkpatrick Model, this review focused on studies that measured communication skills in either simulated or clinical settings. The aim of this systematic review was to examine the effect of experiential communication skills education on GME trainees' communication behaviors. Method: Five databases were searched for studies published between 2001 and 2021 using terms representing the concepts of medical trainees, communication, training, and skills and/or behaviors. Included studies had an intervention design, focused only on GME trainees as learners, used experiential methods, and had an outcome measure of communication skills behavior that was assessed by a simulated or standardized patient (SP), patient, family member, or outside observer. Studies were examined for differences in outcomes based on study design; simulated versus clinical evaluation setting; outside observer versus SP, patient, or family member evaluator; and length of training. Results: Seventy-seven studies were ultimately included. Overall, 54 (70%) studies reported some positive findings (i.e., change in behavior). There were 44 (57%) single-group pre–post studies, 13 (17%) nonrandomized control studies, and 20 (26%) randomized control studies. Positive findings were frequent in single-group designs (80%) and were likely in nonrandomized (62%) and randomized (55%) control trials. Positive findings were likely in studies evaluating communication behavior in simulated (67%) and clinical (78%) settings as well as in studies with outside observer (63%) and SP, patient, and family member (64%) evaluators. Conclusions: This review demonstrates strong support that experiential communication skills education can impact GME trainees' communication behaviors. Marked heterogeneity in communication trainings and evaluation measures, even among subgroups, did not allow for meta-analysis or comparative efficacy evaluation of different studies. Future studies would benefit from homogeneity in curricular and evaluation measures.